Ferrocement composite columns incorporating hollow core filled with lightweight concrete. (1st April 2023) - Eltaly, Boshra A.; Shaheen, Yousry B.; EL-boridy, Ahmed T.; Fayed, Sabry
Highlights: This study focuses on the structural performance of steel mesh reinforced ferrocement columns with lightweight cores. Lightweight core concrete with steel mesh fabric reinforcement was made either using lightweight aerated autoclaved brick aggregate (LAABA) or expanded polystyrene (EP). Impact of core lightweight concrete type, existing steel mesh fabric, column concrete type, existing hollow core and load eccentricity is studied. Structural performance factors such ductility index, failure mechanism, axial vertical and horizontal displacements and ultimate capacity are studied. Abstract: The structural performance of lightweight ferrocement box columns filled with different types of lightweight materials is the subject of this study. The experimental study includes eleven square columns with a side length of 200 × 200 mm and a column height of 1000 mm, and the dimension of the inner box is 100 × 100 mm along the length of the column height. Seven Ferrocement Concrete (FCs) columns and four Conventional Concrete Columns (NWCs) were casted and tested under the influence of axial load and eccentric load, where the load is transferred at 20 % of the column width. The FC columns were reinforced using welded wire meshes as an alternative to conventional stirrups. The main factors include the type of lightweight concrete used for the core, column concrete type, the existing steel mesh fabric, the hollow core, and axial eccentric load. Experimental results showed that the Ferrocement concrete FC and different filling materials and using the WWM instead of the traditional stirrup increased the ultimate load by an average of 35 %, and decreased the vertical and horizontal displacement by an average of 21.4 % and 39.2 %, respectively, compared to the NWC control sample. A new proposed equation was derived for forecasting the ultimate load of hollow core ferrocement concrete columns reinforced with steel meshes. The results closely match the experimental findings of earlier studies.